Beyond Budget, Village Funds and Budget Politics; A Community Service Webinar - Riza Haris Pohan, Zulfikar; Ramli; Efendi, Sumardi; Angkat, Ismail (SEURAYA Jurnal Pengabdian Kepada Masyarakat, 2023)
The widespread issue of misuse of village funds and their ineffective use has made the community pessimistic about the sustainability of village funds. In fact, village funds are in accordance with the mandate of the law and are a continuation of the CDC (Community Driven Development) recommendations after the 1998 crisis. In addition, village funds are believed to have run optimally and have had an impact on national economic resilience and this is the reason why village funds need to be continued . Through village fund webinars between administrative traps and budgetary politics, an attempt was made to socialize the benefits and optimize village funds through the mouthpieces of experts and practitioners. The webinar was carried out with a positive response from the participants. The participants got enlightenment and a new perspective that village funds are not a useless and wasteful act, but are actually effective in supporting development and improving people's welfare.